Functional Cross-Talk of MbtH-Like Proteins During Thaxtomin Biosynthesis in the Potato Common Scab Pathogen Streptomyces scabiei - Li, Yuting; Tahlan, Kapil; Bignell, Dawn R.D. (Frontiers in Microbiology, 2020)
Thaxtomin A is a potent phytotoxin that serves as the principle pathogenicity determinant of the common scab pathogen, Streptomyces scabiei, and is also a promising natural herbicide for agricultural applications. The biosynthesis of thaxtomin A involves the non-ribosomal peptide synthetases (NRPSs) TxtA and TxtB, and an MbtH-like protein (MLP), TxtH, which may function as a chaperone by promoting the proper folding of the two NRPS enzymes in S. scabiei. MLPs are required for the proper function of many NRPS enzymes in bacteria, and they are often capable of interacting with NRPSs from different biosynthetic pathways, though the mechanism by which this occurs is still poorly understood. To gain additional insights into MLP functional cross-talk, we conducted a broad survey of MLPs from diverse phylogenetic lineages to determine if they could functionally replace TxtH. The MLPs were assessed using a protein solubility assay to determine whether they could promote the soluble expression of the TxtA and TxtB adenylation domains. In addition, the MLPs were tested for their ability to restore thaxtomin production in a S. scabiei mutant that lacked TxtH and other endogenous MLPs. Our results showed that the MLPs investigated vary in their ability to exhibit functional cross-talk with TxtH, with two of the MLPs being unable to compensate for the loss of TxtH in the assays performed. The ability of an MLP to serve as a functional partner for the thaxtomin NRPS was not correlated with its overall amino acid similarity with TxtH, but instead with the presence of highly conserved residues. In silico structural analysis of TxtH in association with the TxtA and TxtB adenylation domains revealed that several such residues are situated at the predicted interaction interface, suggesting that they might be critical for promoting functional interactions between MLPs and the thaxtomin NRPS enzymes. Overall, our study provides additional insights into the mechanism of MLP cross-talk, and it enhances our understanding of the thaxtomin biosynthetic machinery. It is anticipated that our findings will have useful applications for both the control of common scab disease and the commercial production of thaxtomin A for agricultural use.